2016
DOI: 10.17235/reed.2016.4211/2016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcome of portal thrombosis in a cohort of cirrhotic patients undergoing liver transplantation

Abstract: Introduction:The prevalence of portal vein thrombosis (PVT) in patients that have undergone liver transplantation (LT) is 9.7% (SD 4.5). The aim of our study was to determine the prevalence, assess the factors that are associated with PVT and clarify their association with prognosis in patients with liver cirrhosis (LC) and LT.Aims and methods: From 2005 to 2014, laboratory, radiological and surgical data were collected from patients with LC in our center who had undergone LT for the first time.Results: One hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Cruz et al[ 22 ] demonstrated that non-alcoholic steato-hepatitis was more frequently associated with PVT (40.48%), followed by hepatitis C virus (23.81%) and autoimmune hepatitis (19.05%), all of these etiologies being characterized by a significant pro-inflammatory status. By contrast, in another study with 199 candidates for LT, no relation was found between the etiology of liver disease and PVT prevalence[ 23 ].…”
Section: Prevalence and Predictors For Non-malignant Pvt: Etiology Ofmentioning
confidence: 96%
“…Cruz et al[ 22 ] demonstrated that non-alcoholic steato-hepatitis was more frequently associated with PVT (40.48%), followed by hepatitis C virus (23.81%) and autoimmune hepatitis (19.05%), all of these etiologies being characterized by a significant pro-inflammatory status. By contrast, in another study with 199 candidates for LT, no relation was found between the etiology of liver disease and PVT prevalence[ 23 ].…”
Section: Prevalence and Predictors For Non-malignant Pvt: Etiology Ofmentioning
confidence: 96%
“…In most cases the operative time is extended, more transfusions are required and there is a greater possibility of reoperation, whereas PVT extension plays a decisive role in the survival rate [ 81 , 82 ]. Generally, overall morbidity and mortality in LT recipients of are not influenced by the presence of PVT [ 83 ]. However, in a recent meta-analysis [ 84 ], it was demonstrated that LT recipients with pre-LT PVT had a significantly lower 1-year survival rate compared to those without (odds ratio [OR] 0.733, 95% confidence interval [CI] 0.621-0.865).…”
Section: Pvt and Ltmentioning
confidence: 99%
“…PVT had been previously described as a factor that increases mortality within 30 days post-transplant (2,30). The study by Ghabril et al (14) that used the OPTN database found that PVT represents an independent mortality risk factor in the first 90 days post-transplant and in graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…Not all the mechanisms involved in the pathophysiology of PVT in cirrhotic patients are well understood. However, selected predictive factors have been described, including reduced portal flow (2), the presence of collateral circulation (4), prior damage to the portal vein system (5) and focal inflammatory injuries (6). Cirrhosis-associated rebalanced hemostasis, where procoagulant factors may predominate, adds to this condition (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation